Re-Formative Polymer Composites from Plastic Waste: Novel Infrastructural Product Application - Richard P. Turner; Catherine A. Kelly; Rod Fox; Bill Hopkins (Recycling, 2018)
A novel re-formative polymer composite manufacturing route has been developed by UK and Qatar-based Universities. This novel process recycles domestic-waste thermoplastic material, without the requirement for intensive filtering or washing operations. The produced polymer can be reinforced with recycled glass fibres, forming a structurally load-bearing composite, which may potentially be suitable for use in applications, including utility poles, railway sleepers, and fencing. Thus, infra-red (IR) analysis showed the presence of polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) in the commingled material. Differential scanning calorimetry (DSC) was used to determine glass transition temperatures and melting temperatures of each of the associated polymer types. Dynamic mechanical thermal analysis (DMTA) was used to determine the storage and loss modulus of the bulk commingled component. Lastly, flexural and tensile strengths of the re-formative polymer with differing proportions of glass fibre were assessed, giving a range of strengths at each glass fibre proportion for possible compositional variation in the polymer type. The recycled polymer is considered a viable structural material for replacing both wooden and concrete components, generating a polymer recycling route with concomitant environmental benefits. This plastic recycling route therefore offers a solution towards achieving climate change targets with a purposeful end-product component.